The Complexities of Decision-making Related to Health Risk Assessments - Knuth, Barbara (Maine Policy Review, 1995)
Maine, like the nation, has focused a great deal of recent attention on determining acceptable levels of environmental and human health risk. Barbara discusses the role and uses of scientific information in risk assessment and public policy debate. Similar to Kevin Boyle’s previous article (featured in the December 1994 issue of Maine Policy Review), Knuth discusses the 1992 Maine Board of Environmental Protection hearings which focused on the human consumption of fish potentially contaminated with dioxin.